1999
DOI: 10.1002/j.1550-8528.1999.tb00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of High‐Calorie, Low‐Nutrient‐Dense Food Consumption among Obese and Non‐Obese Adolescents

Abstract: BANDINI, LINDA G. DUNG VU, AVIVA MUST, HELENE CYR, ALISON GOLDBERG, AND WILLIAM H. DIETZ. Comparison of high-calorie, low-nutrient-dense food consumption among obese and non-obese adolescents. Obes Res. 1999;7:438-443. Objective: The purpose of this study was to determine whether obese adolescents eat more high-calorie lownutrient-dense foods than non-obese adolescents. Research Methods and Procedures: Using a crosssectional design, 22 non-obese and 21 obese adolescents kept 14-day food records. Records provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
3
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 16 publications
11
94
3
7
Order By: Relevance
“…15 Calories from carbohydrate as a percentage of reported energy intake were significantly greater in the non-overweight children compared to the overweight group. Similar results were obtained by Bandini et al 16 By making comparisons to the age þ 5 rule, 22 our results show that the schoolchildren in our sample consumed inadequate dietary fiber (13.2 AE 8.2 g=day). Results of other authors 22,25,26 confirm that the schoolchildren did not consume adequate fiber.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…15 Calories from carbohydrate as a percentage of reported energy intake were significantly greater in the non-overweight children compared to the overweight group. Similar results were obtained by Bandini et al 16 By making comparisons to the age þ 5 rule, 22 our results show that the schoolchildren in our sample consumed inadequate dietary fiber (13.2 AE 8.2 g=day). Results of other authors 22,25,26 confirm that the schoolchildren did not consume adequate fiber.…”
Section: Discussionsupporting
confidence: 89%
“…The energy intake in both groups approximates the Recommended Dietary Allowances, 14 but according to Bandini et al's data, 16 the percentage energy intake reported was significantly lower in the overweight group. In the total sample, the energy intake was lower than reported by other authors.…”
Section: Discussionsupporting
confidence: 53%
“…Otherwise, unhealthy snacking may have a role in the development of overweight/obesity and hypertension. Other studies have however failed to find a relationship between overweight and snacking 49,50 , reporting that obese adolescents eat no more "junk" food than their non-obese peers.…”
Section: Discussionmentioning
confidence: 98%
“…Many cross-sectional studies have shown a positive association between consumption of sweetened beverages, mainly in teenagers, and body weight [58][59][60][61][62][63][64][65] (reviewed in [66]). Interventional studies further showed that adding sweetened beverages to the usual diet led to an increase in body weight [67,68], while reducing sweetened beverages intake in overweight subjects decreased body weight [69][70][71][72][73].…”
Section: Do Changes In Fructose Consumption Explain the Current Epidementioning
confidence: 99%